Sod Busting : How Families Made Farms on the Nineteenth-Century Plains - Danbom, David B., 1947- (Book collections on Project MUSE., 2014)
"Stretching beyond the sweeping accounts typical of standard textbooks, Danbom challenges students to think about the many practicalities of surviving on the Great Plains in the late nineteenth century by providing a detailed account of how settlers acquired land and made homes, farms, and communities. He examines the physical and climatic obstacles of the plains - perhaps America's most inhospitable frontier - and shows how settlers sheltered themselves, gained access to fuel and water, and broke the land for agriculture. Treating the Great Plains as a post-industrial frontier, Danbom delves into the economic motivations of settlers, as well as the physically and economically difficult process of farm making. He explains how settlers got the capital they needed to succeed and how they used the labor of the entire family to survive until farms returned profits. He examines closely the business decisions that determined the success or failure of these farmers in a boom-and-bust economy; details the creation of churches, schools, and service centers that enriched the social and material lives of the settlers; and shows how the support of government, railroads, and other businesses contributed to the success of plains settlement. Based on contemporary accounts, settlers' reminiscences, and the work of other historians, Sod Busting dives deeply into the practical realities of how things worked to make vivid one of the quintessentially American experiences, breaking new land."--Back cover.